Раскопки квартала X в Северном районе Херсонеса - Голофаст, Л.А.; Рыжов, С.Г. (Материалы по археологии, истории и этнографии Таврии, 2003)
Предварительная публикация результатов раскопок кварталов Северного района, в которой дана краткая характеристика застройки как всего района в целом, так и каждого квартала в отдельности, а также найденного при раскопках материала, уже была дана автором раскопок. Целью предлагаемой работы является по возможности полная публикация всего комплекса находок из квартала X и всей имеющейся информации об открытых строительных остатках. The paper presents full information on uncovered building remains and finds produced by the excavations in the quarter X located in the Northern district of Chersonesos. The entire district systematically explored from 1931 is of great interest for the researchers in the field of Late Byzantine town. The excavations of the dwelling quarters abruptly burnt in the third quarter of the 13th century brought to light the complete complex of artifacts that were in use just before the fire thus providing an insight into everyday-life of the residents. Later most part of the district survived intact being neither rebuilt nor overlain by modern constructions.